2009
DOI: 10.1097/olq.0b013e3181a2ad98
|View full text |Cite
|
Sign up to set email alerts
|

Gonococcal, Chlamydia, and Syphilis Infection Positivity Among MSM Attending a Large Primary Care Clinic, Boston, 2003 to 2004

Abstract: Rectal gonorrhea and syphilis seropositivity were frequently diagnosed in asymptomatic MSM; STD prevalence was highest in MSM tested due to an STD exposure or reporting high-risk sex, underscoring the need to promote routine screening in high risk MSM populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 8 publications
4
45
3
1
Order By: Relevance
“…2% incidence of rectal and pharyngeal gonorrhoea was observed in our study, which is lower than that reported by Mathew et al [9] .…”
Section: Discussioncontrasting
confidence: 56%
“…2% incidence of rectal and pharyngeal gonorrhoea was observed in our study, which is lower than that reported by Mathew et al [9] .…”
Section: Discussioncontrasting
confidence: 56%
“…The principal factors influencing the PPV are the prevalence of gonorrhoea in the population tested and variation in the specificity of [26][27][28] • NAATs are significantly more sensitive than culture for detecting pharyngeal and rectal infection [29][30][31][32][33][34][35] and are the test of choice for screening for rectal and pharyngeal gonococcal infection. However, commercially available NAATs are not licensed for testing specimens from these sites and they differ significantly in their specificity, 36,37 particularly at the pharynx due to the frequent presence of non-gonococcal Neisseria • Women may have genital tract infection localized to the endocervix or urethra.…”
Section: Diagnosismentioning
confidence: 99%
“…In the United Kingdom, 82% of sexual health clinics offer asymptomatic MSM screening by NAATs for chlamydia, and 23% are offered NAATs for gonorrhea (2). Several studies using NAATs for the detection of N. gonorrhoeae and C. trachomatis from rectal swab samples have shown a higher burden of disease than would have been detected with traditional assays, including culture (1,6,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In the United Kingdom, 82% of sexual health clinics offer asymptomatic MSM screening by NAATs for chlamydia, and 23% are offered NAATs for gonorrhea (2). Several studies using NAATs for the detection of N. gonorrhoeae and C. trachomatis from rectal swab samples have shown a higher burden of disease than would have been detected with traditional assays, including culture (1,6,(11)(12)(13)(14)(15).Despite a high prevalence of self-reported anal sex in the general population and some high-risk groups, there are no commercially available tests for chlamydia or gonorrhea that have regulatory approval for use with rectal swab samples (1,5,9,14). Problems of cross-reactivity with nongonococcal Neisseria species, which may frequently be found in the lower gastrointestinal tract, may have dissuaded commercial manufacturers from seeking regulatory approval for this sample type.…”
mentioning
confidence: 99%